A study on the potential of electricity generation from wave energy in Pelabuhan Ratu, Sukabumi - Maulana, Putra Bahtiar; Sawiji, Asri (UIN Sunan Ampel Surabaya, 2021)
Pelabuhan Ratu is an area that has high wave energy potential and can be used as renewable energy. Wave energy harness the power of ocean waves into an electrical energy. The purpose of this research is to estimate the potential of wave energy in the month of Muharram and Rajab (Islamic/Hijriyah calendar) in the year 2018. It is based on local communities beliefs that the Muharram month has a high wave characteristic, and in this study compared with Rajab, the other month in Hijriyah calendar. The value of the forecasting waves in Muharram has a higher value compared to the Rajab. The estimated value of the power generated in the Muharram of 634.205 KWatt, whereas in the Rajab of 119.563 KWatt. The value is influenced to the fetch length. This wave energy potential then can be used to estimate the electrical power generated and the effect of the turbine on the application of the Oscillating Water Column (OWC) system.